The ICT Skills of Senior or Vocational School Teacher in Jakarta and Lampung - Munandar, Aris; Cahyana, Ucu; ., Samadi; ., Darsep; ., Budiaman (KnE Social Sciences, 2024)
This research aims to understand the ICT skills and application of senior or vocational school teachers in terms of their educational level, teaching experience, training participation, school accreditation, and region. The method used in this research is a survey. The population of this research are teachers from senior high schools and vocational high schools (whether public or private) that have been accredited a minimum B and are located in the Jakarta and Lampung. Multistage random sampling was used as for sampling. The total sample are 468 teachers from Jakarta and 374 teachers from Lampung. Data were collected through a questionnaire and documentation. Multiple regression was used for the data analysis. The results showed a significance of 0.00 which means there was a weak relations with the R value of 0.311. Partially, the use of ICT is influenced by the level of education, teaching experience, training participation, and regional characteristics. The use of ICT is not influenced by the school’s accreditation. The use of ICT is very personal and doesn’t have any relation to school characteristics. In addition, the use of ICT in Jakarta which is the capital city is higher than Lampung. Keywords: ICT, teacher, region